1965
DOI: 10.3382/ps.0440283
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Phosphorus Requirements of Broiler Chickens

Abstract: A FTER more than 35 years of investi->• gation, there is considerable disagreement in the literature as to the levels of calcium and phosphorus required for optimum performance of growing chickens. A review of the more pertinent literature by Lillie et al. (1964) indicates that the range of discordant values is being narrowed to some extent and that the calcium level recommended by the National Research Council is higher than that which many investigators found to be adequate for optimum growth. The majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 14 publications
(17 reference statements)
3
6
0
Order By: Relevance
“…In this experiment 1.18% Ca produced the greatest gain but 1.0% was sufficient for normal feathering. These results are in agreement with those of Migicovsky et al (1947), and Twining et al (1965) who reported that when the dietary Ca was increased from very low levels, the bone ash improved. The effect of zinc was not consistent, since in the low and high Ca diets no significant differences were observed due to the zinc supplementation but in the inter- mediate Ca levels a significant difference was observed.…”
Section: Resultssupporting
confidence: 93%
“…In this experiment 1.18% Ca produced the greatest gain but 1.0% was sufficient for normal feathering. These results are in agreement with those of Migicovsky et al (1947), and Twining et al (1965) who reported that when the dietary Ca was increased from very low levels, the bone ash improved. The effect of zinc was not consistent, since in the low and high Ca diets no significant differences were observed due to the zinc supplementation but in the inter- mediate Ca levels a significant difference was observed.…”
Section: Resultssupporting
confidence: 93%
“…The results of the present studies indicate a calcium requirement for ducklings that is appreciably lower than the 0.8-1.0% calcium required by the broiler chick (Ed-wards et al, 1963;Mehring and Titus, 1964;Twining et al, 1965). It appears that the duckling is similar to the gosling in terms of its calcium needs.…”
Section: Resultsmentioning
confidence: 36%
“…reported concerning the calcium requirements for growth and bone development of chicks (Hart et al, 1930;Twing et al, 1965;Itoh and Hatano, 1964) and the effect of dietary calcium upon the productive performance of laying hens (Deobald et al, 1936;Petersen et al, 1960;Mehring and Titus, 1964). However, relatively few and often very conflicting investigations have been reported concerning the calcium requirements of pullets from eight weeks to the onset of egg production and concerning the effect of calcium levels during the developing period upon the subsequent production.…”
Section: Introduction C Onsiderable Research Has Beenmentioning
confidence: 94%